A DIFFERENCES IN ACHIEVEMENT MOTIVATION IN PHYSICAL EDUCATION (PJOK) BETWEEN MALE AND FEMALE STUDENTSAT SMAN 1 SOURCE - Ferdiana, DhonaChindy (JUARA : Jurnal Olahraga, 2023)
Research entitled "Differences in Achievement Motivation in Physical Education (PJOK) between male and female students at SMAN 1 SUMBER". This research is a descriptive study with a cross-sectional approach. The researcher used a cross-sectional design because the researcher intended to identify whether or not there was a relationship between the independent variable (achievement motivation) and the dependent variable (male and female students) in one measurement using a questionnaire measuring instrument. The instrument used is an achievement motivation scale related to physical education, according to the original name adopted in this research. The original name of the instrument is Learning and Performance Orientation in Physical Education Classes Questionnaire (LAPOPECQ).